Balanced development as a basis of polish ecological politics, in searching of the new formula of the compromise between ecology and economy - Rudnicki, Maciej (Studia Ecologiae et Bioethicae, 2007)
The article includes detailed analysises of basic terms and concepts, especially the phrases: balanced development, ecological politics, compromise, ecology, economy, these analysises show the rich context of international science researches, European Union, Poland and they present wide historical and contemporary aspect.